The afterlife of Mal Caldera - Perez, Nadi Reed (Titan Books, 2024)
"Mal Caldera--former rockstar, retired wild-child and excommunicated black sheep of her Catholic family--is dead. Not that she cares. She only feels bad that her younger sister, Cris, has been left to pick up the pieces Mal left behind. While her fellow ghosts party their afterlives away at an abandoned mansion they call the Haunt, Mal is determined to make contact with Cris from beyond the grave. She enlists the help of a reluctant local medium, Ren, and together, they concoct a plan to pass on a message to Cris. But the more time they spend together, the more they begin to wonder what might have been if they'd met before Mal died. Mal knows it's wrong to hold on so tightly to her old life. Bad things happen to ghosts who interfere with the living, and Mal can't help wondering if she's hurting the people she loves by hanging around, haunting their lives. But Mal has always been selfish, and letting go might just be the hardest thing she's ever had to do"--